Antimicrobial and Antibiofilm Activity against Staphylococcus aureus of Opuntia ficus-indica (L.) Mill. Cladode Polyphenolic Extracts - Federica Blando; Rossella Russo; Carmine Negro; Luigi De Bellis; Stefania Frassinetti (MDPI AG, 2019)
Plant extracts are a rich source of natural compounds with antimicrobial properties, which are able to prevent, at some extent, the growth of foodborne pathogens. The aim of this study was to investigate the potential of polyphenolic extracts from cladodes of Opuntia ficus-indica (L.) Mill. to inhibit the growth of some enterobacteria and the biofilm formation by Staphylococcus aureus. Opuntia ficus-indica cladodes at two stages of development were analysed for total phenolic content and antioxidant activity by Oxygen Radical Absorbance Capacity (ORAC) and Trolox equivalent antioxidant capacity (TEAC) (in vitro assays) and by cellular antioxidant activity in red blood cells (CAA-RBC) (ex vivo assay). The Liquid Chromatography Time-of-Flight Mass Spectrometry (LC/MS−TOF) analysis of the polyphenolic extracts revealed high levels of piscidic acid, eucomic acid, isorhamnetin derivatives and rutin, particularly in the immature cladode extracts. Opuntia cladodes extracts showed a remarkable antioxidant activity (in vitro and ex vivo), a selective inhibition of the growth of Gram-positive bacteria, and an inhibition of Staphylococcus aureus biofilm formation. Our results suggest and confirm that Opuntia ficus-indica cladode extracts could be employed as functional food, due to the high polyphenolic content and antioxidant capacity, and used as natural additive for food process control and food safety.